2020
DOI: 10.1002/cncy.22256
|View full text |Cite
|
Sign up to set email alerts
|

The utilization and utility of immunostains in body fluid cytology

Abstract: BACKGROUND: Body fluid cytology (BFC) is an important tool in the diagnosis and staging of malignancy and is aided by the judicious use of immunohistochemistry (IHC). The aim of this study was to determine the usage rates of IHC stains in BFC, their type and indications, and their diagnostic impact. We also attempted to estimate the optimal rate of IHC use in BFC by comparing the entire laboratory's and each individual cytopathologist's IHC use rates with their respective indeterminate and malignant diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Although IHC is a widely available and relatively inexpensive ancillary test for characterizing cells in cytologic preparations, equivocal IHC may often result from technical issues, 14 a paucity of cells for staining, heterogeneous expression of markers, or an altered immunoprofile of the tumor cells 15 . Some studies have suggested that the level of expertise of the cytopathologist evaluating the specimen may correlate with the number of IHC stains requested and may play a role in higher rates of indeterminate diagnoses in serous effusion specimens 16 . In our cohort of cases, IHC stains were requested in 11 AUS and 18 SFM cases by a pathologist with <10 years of practice experience versus 8 AUS and 11 SFM cases by a pathologist with >10 years of practice experience.…”
Section: Discussionmentioning
confidence: 99%
“…Although IHC is a widely available and relatively inexpensive ancillary test for characterizing cells in cytologic preparations, equivocal IHC may often result from technical issues, 14 a paucity of cells for staining, heterogeneous expression of markers, or an altered immunoprofile of the tumor cells 15 . Some studies have suggested that the level of expertise of the cytopathologist evaluating the specimen may correlate with the number of IHC stains requested and may play a role in higher rates of indeterminate diagnoses in serous effusion specimens 16 . In our cohort of cases, IHC stains were requested in 11 AUS and 18 SFM cases by a pathologist with <10 years of practice experience versus 8 AUS and 11 SFM cases by a pathologist with >10 years of practice experience.…”
Section: Discussionmentioning
confidence: 99%
“…The cytology of effusions is not restricted to morphology. Microscopic examination is followed by special stains, immunohistochemical stains or flow cytometry, according to the initial morphologic findings [ 5 , 6 ]. In malignant effusions, the classification of the neoplasm as primary (mesothelioma) or secondary (metastasis) is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Cell block preparation and IHC have been found to be of optimal value in only 10-012% of fuids (in a population with relatively low prevalence of maliynancy), above which their diaynostic utility diminishes. [9] Te sensitivity and specifcity of IHC in detection of maliynancy in body fuid has yet not exceeded 90%. [20] [21] Artifcial neural networks have emeryed as a useful decision support tool in cytopatholoyy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunohistochemical markers such as CEA siynifcantly enhance the diaynostic efcacy: a combination of calretinin neyative and CEA positive staininy showed 97% sensitivity and 100% specifcity for maliynancy in one study of 50 cell blocks. [8] But in a larye case series of 5.5 years, it was also shown that use of IHC markers produces a hiyher rate of indeterminate but not maliynant diaynosis [9] , thus undermininy the utility of IHC.…”
Section: Introductionmentioning
confidence: 99%